Minimal treatment options with one-piece implants - Agbaje, Jimoh Olubanwo; Mohamad, El Moheb; Diederich, Henri (Archives of Case Reports, 2021)
The aim of this publication is to present case reports to show what is possible with pterygoid implants for the rehabilitation of edentulous space in the jaw (maxilla) while avoiding sinus lifts and bone grafting procedures. In addition, the added value of one-piece implants for screwed retention is elucidated.